2016
DOI: 10.1101/090340
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

foxQ2 evolved a key role in anterior head and central brain patterning in protostomes

Abstract: This is true for the two major lineages of bilaterian animals, the deuterostomes (including sea urchin 35 and humans) and protostomes (including annelids and insects) and the cnidarians (e.g. the sea 36 anemone), which are representatives of more ancient animals. However, the interaction of these 37 genes has been studied in deuterostomes and cnidarians but not in protostomes. Here, we present 38 the first study the function of the gene foxQ2 in protostomes. We found that the gene acts at the top 39 level of t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Amphioxus embryos also show earlier onset of foxQ2 expression (Kozmik et al, 2007;Yu et al, 2003). The foxQ2 expression in the six3/6-free region has also been reported in protostomes (Kitzmann et al, 2017;Marlow et al, 2014;Martín-Durán et al, 2015;Santagata et al, 2012). In addition, a recent study of embryos of another echinoderm (starfish) has reported that Six3 knockdown-embryos still express foxQ2 at the gastrula stage (Cheatle Jarvela, Yankura, & Hinman, 2016), although it is possible that the regulatory relationship was modified after the diversification of sea urchin and starfish.…”
mentioning
confidence: 89%
See 4 more Smart Citations
“…Amphioxus embryos also show earlier onset of foxQ2 expression (Kozmik et al, 2007;Yu et al, 2003). The foxQ2 expression in the six3/6-free region has also been reported in protostomes (Kitzmann et al, 2017;Marlow et al, 2014;Martín-Durán et al, 2015;Santagata et al, 2012). In addition, a recent study of embryos of another echinoderm (starfish) has reported that Six3 knockdown-embryos still express foxQ2 at the gastrula stage (Cheatle Jarvela, Yankura, & Hinman, 2016), although it is possible that the regulatory relationship was modified after the diversification of sea urchin and starfish.…”
mentioning
confidence: 89%
“…By contrast, little is known about the positive regulation of foxQ2 . Previous analyses have suggested that Six3/6 contributes to the activation of foxQ2 in sea urchin Strongylocentrotus purpuratus (Wei, Yaguchi, Yaguchi, Angerer, & Angerer, ), red flour beetle (Kitzmann et al, ), and sea anemone (Sinigaglia et al, ), but the Six3/6‐mediated regulation is not sufficient to explain the expression pattern of foxQ2 in some cases. In fact, in sea urchin embryos, the onset of six3/6 expression seems to be later than that of foxQ2 (Materna, Nam, & Davidson, , our unpublished data), and expression domains of six3/6 and foxQ2 become separated at the later stage (Howard‐Ashby et al, ; Wei et al, ; Yaguchi et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations